2005
DOI: 10.1002/ijc.21614
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones stimulate human prostate cancer progression and metastasis

Abstract: Tissue recombinants (TRs) composed of mouse urogenital mesenchyme (mUGM) plus an immortalized nontumorigenic human prostatic epithelial cell line (BPH-1) were grown under the kidney capsule of male athymic nude mice under different hormonal conditions. The objectives were to determine temporal plasma concentrations of testosterone (T) and estradiol-17b (E 2 ) that elicit progression of nontumorigenic human prostatic epithelial cells in vivo. Second, to determine whether mUGM1BPH-1 TRs in [T1E 2 ]-treated hosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 29 publications
(23 reference statements)
5
115
0
2
Order By: Relevance
“…In prostatic carcinoma, the tumor stroma is constituted mainly of fibroblastic and myofibroblastic cells (Cunha et al, 2003), suggesting that cell-transition changes have occurred in both the stroma and the epithelium during tumorigenesis. Earlier tissue recombination studies by Thompson et al (1993) have indicated that prostatic tumorigenesis indeed requires changes in both the stroma and the epithelium, a notion supported by the results of Cunha and co-workers (Olumi et al, 1999;Wang et al, 2001;Cunha et al, 2003;Ricke et al, 2006). Thus, prostate cancer-associated fibroblasts could promote tumor transformation of the epithelial BPH-1 cells that are immortalized with SV40 Tag (Olumi et al, 1999;Wang et al, 2001).…”
Section: Ar Dual Functions In Prostate Cancer Progression and Metastasismentioning
confidence: 88%
See 1 more Smart Citation
“…In prostatic carcinoma, the tumor stroma is constituted mainly of fibroblastic and myofibroblastic cells (Cunha et al, 2003), suggesting that cell-transition changes have occurred in both the stroma and the epithelium during tumorigenesis. Earlier tissue recombination studies by Thompson et al (1993) have indicated that prostatic tumorigenesis indeed requires changes in both the stroma and the epithelium, a notion supported by the results of Cunha and co-workers (Olumi et al, 1999;Wang et al, 2001;Cunha et al, 2003;Ricke et al, 2006). Thus, prostate cancer-associated fibroblasts could promote tumor transformation of the epithelial BPH-1 cells that are immortalized with SV40 Tag (Olumi et al, 1999;Wang et al, 2001).…”
Section: Ar Dual Functions In Prostate Cancer Progression and Metastasismentioning
confidence: 88%
“…Thus, prostate cancer-associated fibroblasts could promote tumor transformation of the epithelial BPH-1 cells that are immortalized with SV40 Tag (Olumi et al, 1999;Wang et al, 2001). Similarly, urogenital mesenchymes from rat and mouse could also elicite tumor transformation in BPH-1 cells in the presence of testosterone and 17b-estradiol (E2) (Wang et al, 2001;Ricke et al, 2006). However, cancer-associated fibroblasts in a castrated host and urogenital mesenchyme from testicular feminized mice (a mouse without functional AR) were unable to promote tumor transformation from BPH-1 cells (Ricke WA, personal communication).…”
Section: Ar Dual Functions In Prostate Cancer Progression and Metastasismentioning
confidence: 99%
“…It is noteworthy that although the prostate is exquisitely sensitive to androgens, administration of high doses of T alone in this model is insufficient to drive tumorigenesis. Instead, estrogens are required to act in synergy with androgens to induce tumor formation [38], mediated through estrogen receptor a expressed in the stromal cells [23]. Both of these approaches highlight the active role played by stroma in the process of tumorigenesis in the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ''initiation events'' were the basis for their selection as the epithelial source for these studies, since this instability facilitates induction of malignancy in response to CAFs and/or hormonal carcinogenesis; normal epithelial cells from primary specimens are not susceptible to carcinogenesis using these assays [13,38]. While there are key differences between BPH-1 cells and primary epithelial cells, including the methylation of the CD133, with silencing of up to 50% of BPH-1 cells [39], our data are supported by several previous studies in mice [4] and in primary human cells [3] showing that basal cells are a cell of origin of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional uptake and blood supply from surrounding and endothelial cells are very important in PCa cell growth and invasion [7,71]. The inflammatory cells also infiltrate the prostate and can cause prostatitis, which can alter PCa cell growth and metastasis.…”
Section: In Vivo Tissue Recombination Modelmentioning
confidence: 99%